Trace elements ebook - Leon, Donna (Commissario Brunetti, 2020)
The New York Times –bestselling author of Unto Us a Son Is Given continues “o ne of the most exquisite and subtle detective series ever ” ( The Washington Post ).   When a dying hospice patient gasps that her husband was murdered over “bad money,” Commissario Brunetti softly promises he and his colleague, Claudia Griffoni, will look into what initially appears to be a private family tragedy. They discover that the man had worked in the field, collecting samples of contamination for a company that measures the cleanliness of Venice’s water supply, and that he had recently died in a mysterious motorcycle accident. Piecing together the tangled threads, Brunetti comes to realize the perilous meaning in the woman’s accusation and the threat it reveals to the health of the entire region. But justice in this case proves to be ambiguous, as Brunetti is reminded it can be when he reads Aeschylus’s classic play The Eumenides .   Praise for Donna Leon’s Commissario Brunetti Mysteries   “[Leon] has never become perfunctory, never failed to give us vivid portraits of people and of Venice, never lost her fine, disillusioned indignation.” —Ursula K. LeGuin, author of Dancing at the Edge of the World   “You become so wrapped up in these compelling characters. . . . Each one is better than the last.” —Louise Erdrich, winner of the National Book Award for Fiction   “Leon’s Venetian mysteries never disappoint, calling up the romantic sights and sounds of La Serenissima even as they acquaint us with the practical matters that concern the city’s residents.” — The New York Times Book Review   “The sophisticated but still moral Brunetti, with his love of food and his loving family, proves a worthy custodian of timeless values and verities.” — The Wall Street Journal